2006
DOI: 10.1097/01.olq.0000194597.16236.48
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of HIV Partner Counseling and Referral Services: Client and Provider Attitudes, Preferences, Practices, and Experiences

Abstract: Considering that clients have positive attitudes toward self- and provider referral, local HIV prevention programs need to ensure that all HIV-positive clients are offered partner notification services. Additional research is needed to assess the potential risks of notifying partners and to identify effective techniques to improve client and provider participation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 30 publications
4
41
0
Order By: Relevance
“…Statistically significant differences in HIV test result were found across the three testing strategies (χ 2 (2)=18.31, p< 0.001). As shown in Table 2, the positivity rate for men tested via alternative venue testing was 6.3% (n=25) compared to 19.3% (n=21) for men tested via the social networks strategy and 14.3% (n=7) for men tested via partner services. There was no statistically significant difference in HIV test results for men tested via the social networks strategy and partner services (OR=1.43, 95% CI=0.56, 3.64).…”
Section: Hiv Test Results By Testing Strategymentioning
confidence: 93%
See 1 more Smart Citation
“…Statistically significant differences in HIV test result were found across the three testing strategies (χ 2 (2)=18.31, p< 0.001). As shown in Table 2, the positivity rate for men tested via alternative venue testing was 6.3% (n=25) compared to 19.3% (n=21) for men tested via the social networks strategy and 14.3% (n=7) for men tested via partner services. There was no statistically significant difference in HIV test results for men tested via the social networks strategy and partner services (OR=1.43, 95% CI=0.56, 3.64).…”
Section: Hiv Test Results By Testing Strategymentioning
confidence: 93%
“…Partner services is a public health strategy that involves identifying, locating, and interviewing HIV-infected persons (index patients) to elicit names and contact information of their sex and needle-sharing partners, notifying partners of their exposure to HIV, and providing HIV counseling, testing, and referral services to those partners [15]. Research suggests that partner services is effective for recruiting partners into testing services and identifying previously undiagnosed HIV-positive individuals [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Although data on sexual partner notification practices among HIV-infected patients receiving HIV care exist(5-10), little is known about whether these practices vary based on risk of HIV transmission as determined by HIV viral load. Moreover, there is a paucity of data specifically on the practices among men(11).…”
Section: Introductionmentioning
confidence: 99%
“…In 2008, the Centers for Disease Control and Prevention (CDC) published revised guidance on PS and encouraged the coordination of these activities for HIV, syphilis, gonorrhea, and chlamydia. 1 While HIV PS has been shown to be cost-effective [2][3][4] and is well accepted by the communities served, [5][6][7] uptake of HIV PS has been slow. A survey of U.S. health departments with the highest HIV and sexually transmitted disease (STD) morbidity in 2006 found that HIV PS was more common than in 2001, and nearly all surveyed jurisdictions provided HIV PS to those diagnosed with HIV in municipal STD clinics.…”
mentioning
confidence: 99%